Biology of fall armyworm fed on leaves of corn cultivated on soil previously corrected for different aluminum levels. - Oliveira, Lenita J.; Parra, José Roberto P.; Cruz, Ivan (Pesquisa Agropecuaria Brasileira, 2014)
Biological aspects related to the fall armyworm (Spodoptera frugiperda (J.E. Smith, 1797) were studied in the Laboratory, at Sete Lagoas, MCL Brazil. Larvae were fed ou excised leaves from a susceptible corn cultivated on a cerrado type soil previously corrected for there Al levels (low = 0.15 meq/cm3; medium = 0.8 meq/100 cm3 and high = 1.4 meq/ 100 cm). A complete randomized design with 100 replications was used, being one newly born larva per replication, placed inside a plastic cup of 50 ml. To observe the reproduction, were utilized 15 couple, each of them placed in a PVC container. It was concluded that the level of Al affected the biology of the insect. When this level was low, the larval period was shorter. The 4th instar was the most sensitive and could be used as a standard parameter of comparion for this type of study. The fertility Efe table showed that the leaves produced from soil with high level of Al were less favorable to the insect